2024
DOI: 10.1037/rev0000405
|View full text |Cite
|
Sign up to set email alerts
|

Conditioned inhibition, inhibitory learning, response inhibition, and inhibitory control: Outlining a conceptual clarification.

Abstract: Inhibition can be defined as a phenomenon in which an agent prevents or suppresses a behavioral state that would otherwise occur. Associative learning studies have extensively examined how experiences shape the acquisition of inhibitory behavioral tendencies across many species and situations. Associative inhibitory phenomena can be studied at various levels of analysis. One could focus on the trajectory of behavioral change involved in learning from negative statistical associations between discrete events (i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 257 publications
0
15
0
Order By: Relevance
“…The subsequent, although perhaps unjustified, a posteriori analysis, argues that this difference is transient and only appears on trial one and that there is little difference between treatments on subsequent trials. difference suggests that a preventative (or inhibitory) association may extinguish more rapidly than the generative (or excitatory) association (see also Baetu & Baker, 2010;Sosa, 2022).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The subsequent, although perhaps unjustified, a posteriori analysis, argues that this difference is transient and only appears on trial one and that there is little difference between treatments on subsequent trials. difference suggests that a preventative (or inhibitory) association may extinguish more rapidly than the generative (or excitatory) association (see also Baetu & Baker, 2010;Sosa, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Rather than a direct test of learning, this learning is demonstrated by the ability to enhance a secondary cue. This method differentiates inhibition, the active suppression of excitatory learning (see Sosa, 2022), from the failure to learn about a stimulus. Across the experiments, we replicated findings of generative enhanced learning in humans (Lovibond et al, 1988) and showed that this second-order effect can be induced using a go/no-go paradigm.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the case of rewarded or positively reinforced behavior our dual-system theory (Perez & Dickinson, 2020) proposed that the habit system employed a standard prediction-error learning algorithm that, when applied to habit learning reinforced by a safety signal, should reflect the difference between the strength of Pavlovian inhibition elicited by the feedback stimuli at the time when a response is performed and the current habit strength. In the absence of an agreed theory of Pavlovian inhibitory learning (Sosa, 2022), however, the development of a computational theory of habitual avoidance learning would be highly arbitrary.…”
Section: Discussionmentioning
confidence: 99%